Dietary sodium intake and the risk of airway hyperreactivity in a random adult population. - Britton, J; Pavord, I; Richards, K; Knox, A; Wisniewski, A; Weiss, S; Tattersfield, A (BMJ Publishing Group, 1994)
BACKGROUND: High dietary sodium intake has been identified as a potential cause of asthma and airway hyperreactivity. This study was designed to test the hypothesis that dietary sodium intake is an independent determinant of the risk of hyperreactivity in the general population, and to assess the role of atopy in the association between these factors. METHODS: Airway reactivity to methacholine, atopy, 24 hour urinary sodium excretion, and self-reported smoking and symptom history were measured in a random sample of 1702 adults aged 18-70 from an administrative district of Nottingham. Hyperreactivity was defined as a PD20FEV1 of 12.25 mumol or less, and atopy was defined quantitatively as the mean allergen skin weal response to Dermatophagoides pteronyssinus, cat fur, and grass pollen, and categorically as the occurrence of any allergen response 1 mm or greater than the saline control. Multiple logistic regression analysis was used to estimate the independent relative odds of hyperreactivity, atopy, or symptoms in relation to sodium excretion in all 1702 subjects, and multiple linear regression to assess the independent relation between sodium excretion and mean allergen skin weal diameter, and the PD20 value amongst hyperreactive subjects. RESULTS: There was no relation between the relative odds of hyperreactivity to methacholine and 24 hour urinary sodium excretion, either before or after adjustment for age, smoking, allergen skin weal diameter, and sex, and similarly no relation if the analysis was restricted to men or women only. The relative odds of having at least one allergen skin test response 1 mm greater than the saline control were increased in relation to sodium excretion after adjustment for age, sex, and smoking by a ratio of 2.08 (95% CI 1.04 to 4.15) per log10 unit increase in sodium excretion, but there was no evidence of an association between sodium excretion and the occurrence of self-reported wheeze, hay fever, eczema, or asthma. There was no relation between 24 hour sodium excretion and the magnitude of the mean allergen skin weal response or the PD20 value. CONCLUSIONS: These findings do not support the hypothesis that a high dietary sodium intake is a risk factor for airway hyperreactivity or atopic disease in the general adult population.